HDAC6-dependent deacetylation of AKAP12 dictates its ubiquitination and promotes colon cancer metastasis. (28th November 2022) - Deng, Yilin; Gao, Jinjin; Xu, Guangying; Yao, Yuan; Sun, Yan; Shi, Yehui; Hao, Xishan; Niu, Liling; Li, Hui
Abstract: Aberrant expression of histone deacetylase 6 (HDAC6) is greatly involved in neoplasm metastasis, which is a leading cause of colon cancer related death. Thus, deep understanding of the regulatory mechanisms of HDAC6 in the metastasis of colon cancer is warranted. In this study, we firstly found that HDAC6 expression was highly expressed in metastatic colon cancer tissues and inhibition or knockdown of HDAC6 suppressed colon cancer metastasis. Next, based on proteomic analysis we uncovered A-kinase anchoring protein 12 (AKAP12) was a novel substrate of HDAC6. HDAC6 interacted with AKAP12 and deacetylated the K526/K531 residues of AKAP12. Moreover, deacetylation of AKAP12 at K531 by HDAC6 increased its ubiquitination level, which facilitated AKAP12 proteasome-dependent degradation. Importantly, we observed an inverse correlation between AKAP12 and HDAC6 protein levels with human colon cancer specimens. Further deletion of AKAP12 in HDAC6 knockdown cells restored the cell motility defects and reactivated the protein kinase C isoforms, repression of which were responsible for the inhibition of cancer metastasis of AKAP12. Our study identified AKAP12 was a new interactor and substrate of HDAC6 and uncovered a novel mechanism through which HDAC6-dependent AKAP12 deacetylation led to its ubiquitination mediated degradation and promoted colon cancer metastasis. Highlights: We identify AKAP12 as an interactor and substrate of HDAC6. HDAC6-mediated deacetylation of AKAP12 leads to its degradation by the ubiquitin-proteasome system, in turn promoting metastasis. AKAP12 downregulation mechanisms in cancers are governed by potentially existing PTM code.